MENTORING STYLES AND THEIR CONTRIBUTION TO PEDAGOGICAL AND DIDACTIC COMPETENCE DEVELOPMENT - Čiučiulkienė, Nijolė; Mičiulienė, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The current educational theoretical and practical discourse intensively highlights the issue of the relationship between the mentor and mentee, in other words, the style of mentoring. The issue of influence of mentoring style to the development of mentees’ pedagogical and didactic competencies is still not sufficiently investigated. The purpose of the study is to explore mentoring styles and examine their contribution to the development of pedagogical didactic competencies of mentees. Reflective reports of student teachers (N=10) who had their internship practice in secondary schools, were analyzed using content (deductive) analysis method. The findings suggest that emerging mentoring style depends on the age and the previous pedagogical experience of mentee’s: young and having no pedagogical practice mentees tend to follow the traditional-hierarchical mentoring relationship, while older and with some pedagogical experience mentees prefer to practice reciprocal relationship with their mentors. Anyway, in both highlighted cases, the emphasis of mentors is placed on the development of didactical competencies rather than pedagogical. The prevailing mentor – mentee relationship in secondary education and implications for the professional identity of student teachers are discussed as well.